Roles of neutrophils in the regulation of the extent of human inflammation through delivery of IL‐1 and clearance of chemokines. Issue 1 (1st January 2013) - Basran, Alexander; Jabeen, Maisha; Bingle, Lynne; Stokes, Clare A.; Dockrell, David H.; Whyte, Moira K. B.; Walmsley, Sarah R.; Higgins, Kathryn R.; Vogel, Stefanie N.; Wilson, Heather L.; Prince, Lynne R.; Prestwich, Elizabeth C.; et al.
Abstract : Endotoxin‐induced neutrophil recruitment in humans and its potential regulation by CXCL8 clearance. Abstract : This study examined the establishment of neutrophilic inflammation in humans. We tested the hypotheses that neutrophil recruitment was associated with local CXCL8 production and that neutrophils themselves might contribute to the regulation of the size of the inflammatory response. Humans were challenged i.d. with endotoxin. Biopsies of these sites were examined for cytokine production and leukocyte recruitment by qPCR and IHC. Additional in vitro models of inflammation examined the ability of neutrophils to produce and sequester cytokines relevant to neutrophilic inflammation. i.d. challenge with 15 ng of a TLR4‐selective endotoxin caused a local inflammatory response, in which 1% of the total biopsy area stained positive for neutrophils at 6 h, correlating with 100‐fold up‐regulation in local CXCL8 mRNA generation. Neutrophils themselves were the major source of the early cytokine IL‐1β. In vitro, neutrophils mediated CXCL8 but not IL‐1β clearance (>90% clearance of ≤2 nM CXCL8 over 24 h). CXCL8 clearance was at least partially receptor‐dependent and modified by inflammatory context, preserved in models of viral infection but reduced in models of bacterial infection. In conclusion, in a human inflammatory model, neutrophils are rapidly recruited and may regulate the size and outcome of the inflammatory response through the uptake and release of cytokines and chemokines in patterns dependent on the underlying inflammatory stimulus.